2018
DOI: 10.1080/09540121.2018.1524564
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study on alcohol consumption and HIV treatment adherence among men living with HIV in Ugandan fishing communities

Abstract: Ugandan fishing communities are dually burdened with high rates of HIV and alcohol use. This qualitative study explores context and motivation of alcohol consumption, and alcohol’s effect on antiretroviral treatment (ART) adherence, among male fisherfolk living with HIV in Wakiso District, Uganda. We conducted in-depth semi-structured interviews with 30 men in HIV care and on ART, and used a thematic analysis approach for analysis. Alcohol use was identified as a major barrier to ART adherence through cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…While this study was only conducted in three fishing communities in Uganda, the patterns of drinking observed in this study have been seen in other fishing communities throughout East Africa. It is likely the findings and recommendations presented here are generalizable to similar communities (Kiwanuka et al, 2017;Sileo et al, 2016Sileo et al, , 2019Smolak, 2014). Utilizing the SEM and TPT models together has allowed us to contextualize problematic drinking behaviors through both time (TPT) and space (SEM).…”
Section: Discussionmentioning
confidence: 82%
“…While this study was only conducted in three fishing communities in Uganda, the patterns of drinking observed in this study have been seen in other fishing communities throughout East Africa. It is likely the findings and recommendations presented here are generalizable to similar communities (Kiwanuka et al, 2017;Sileo et al, 2016Sileo et al, , 2019Smolak, 2014). Utilizing the SEM and TPT models together has allowed us to contextualize problematic drinking behaviors through both time (TPT) and space (SEM).…”
Section: Discussionmentioning
confidence: 82%
“…In addition, while several studies have suggested marijuana and khat may be prevalent in these communities [9, 18], very few men reported drug use. While this in part could be explained by underreporting, a qualitative exploration of changes in men’s drinking since diagnosis (reported elsewhere) revealed men in our sample had made significant efforts to reduce their consumption since diagnosis [45]. Yet hazardous drinking was prevalent among those who do drink; one-third of the overall sample, and two-third of those who drink, were classified as hazardous drinkers on the AUDIT.…”
Section: Discussionmentioning
confidence: 83%
“…), social status (purchase of alcohol evokes economic capability), and peer pressure; at the community level, the widespread availability of alcohol and the importance of the alcohol business for the local economy, culture of heavy drinking, and lack of accountability by local leaders have been documented. At the policy and societal level, lack of enforcement of national laws to restrict alcohol use emerged as an important factor [ 58 , 60 63 , 69 ]. The authors also documented the widespread belief that “everybody drinks” and a “life is short mentality” (due to the danger of fishing activities) as key contributors to alcohol use in fishing communities [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sileo et al (2019) identified alcohol consumption as one of the main barriers to ART adherence. Alcohol affected adherence through multiple pathways, including cognitive impairment (forgetting to take medication), staying out too late drinking while their ARV medication was at home, and intentionally skipping doses when drinking [ 69 ]. Barriers to accessing HIV treatment and care services included poor transport system [ 76 ], competing needs for work during clinic hours, stigma, low quality of care, and low social support [ 77 ].…”
Section: Resultsmentioning
confidence: 99%